2016
DOI: 10.1002/ana.24608
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features in anterior visual pathway in neuromyelitis optica

Abstract: Severe and widespread neuroaxonal damage and unique dynamics of astrocytes/Müller cells with alterations of AQP4 were prominent in the AVP and may be associated with poor visual function and prognosis in NMOsd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 52 publications
(134 reference statements)
7
93
0
Order By: Relevance
“…Involvement of the optic nerves and the spinal cord in NMO is associated with severe visual impairment and poor prognosis of optic neuritis79 or more severe motor/sensory disabilities for myelitis, in comparison to the respective changes seen in MS. A severe phenotype of NMO is associated with profound tissue damage including neuroaxonal injury, occurring as a secondary consequence of astrocyte damage by AQP4 antibodies. Related to optic neuritis as a representative NMO lesion, the pathological correlates of the severity in NMO have been provided as follows:79 (1) Longitudinally extensive optic neuritis.…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
See 3 more Smart Citations
“…Involvement of the optic nerves and the spinal cord in NMO is associated with severe visual impairment and poor prognosis of optic neuritis79 or more severe motor/sensory disabilities for myelitis, in comparison to the respective changes seen in MS. A severe phenotype of NMO is associated with profound tissue damage including neuroaxonal injury, occurring as a secondary consequence of astrocyte damage by AQP4 antibodies. Related to optic neuritis as a representative NMO lesion, the pathological correlates of the severity in NMO have been provided as follows:79 (1) Longitudinally extensive optic neuritis.…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
“…Related to optic neuritis as a representative NMO lesion, the pathological correlates of the severity in NMO have been provided as follows:79 (1) Longitudinally extensive optic neuritis. (2) Unique dynamics of AQP4, including (i) loss of AQP4 immunoreactivity on astrocytes and complement activation in optic neuritis lesions, (ii) loss of AQP4 immunoreactivity on Müller cells and no complement activation and (iii) densely packed AQP4 immunoreactivity on astrocytes in gliosis at sites of secondary anterograde/retrograde degeneration in the optic nerves and RNFL.…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, she demonstrated severe and widespread neuroaxonal damage, including increased mitochondrial content with unique dynamics of AQP4 expression on astrocytes in the optic nerve and M€ uller cells in the retina. 2 These findings suggested that neurodegeneration in the optic nerve might be associated with the poor recovery of visual function in patients with NMO. The next session was a poster session for submitted abstracts.…”
mentioning
confidence: 97%